Studies on the Influence of Moisture and Spedfic Gravity on the Strength Properties of Mango Wood (Mangifera indica) - NAIR, N UNNIKRISHNAN; RAVINDRAN, K; PILLAI, A. G. GOPALAKRISHNA (Fishery Technology, 2017)
Influence of moisture and specific gravity on the strength of mango wood isdiscussed. The co-efficient of correlation between specific gravity and breakingstrength was found to be nonsignificant. The relation of strength and moisturewas found to be highly significant. The mean strength values indicated a reductionin strength when the moisture increased from 8.5 to 18.8 %. However noappreciable diff~rence in strength values could be observed when moisture increased above 37%. The strength-moisture relationship is a straight line, passingapproximately through the fibre saturation point. By using the exponentialformula, the breaking strength corresponding to any moisture level between zeroand fibre saturation can be determined.